Inside Front Cover: Analytical lifecycle management approach: Application to development of a reliable LC method for estimation of lacidipine. Issue 1 (25th January 2019) - Panda, Sagar Suman; Bera, Ravi Kumar Venkata Varaha; Acharjya, Sasmita Kumari; Sahoo, Padmalaya; Beg, Sarwar
Abstract : Sep Sci plus 2019;2:18–25. DOI:10.1002/sscp.201800110 The cover picture shows the holistic ALM approach for developing an efficient liquid chromatographic method for estimating lacidipine present in pharmaceuticals. This approach established ATP & CQAs for the method, identified the CMVs using QRM tools and employed DoE domain for optimizing the chromatographic process. Further, demarcation of control space and subsequent continual monitoring developed a rapid, robust and reliable analytical method for lacidipine with federal flexibilities.